Дюймовочка и другие сказки: сказки / ред. В. Гетцель - Гетцель В. (Читаем детям, 2011)
Экземпляры: ф-21 (20200316) / Инвентарный номер: 55137 / Цена: 45.00 / Сис.шифр: Д / Авт.знак: Д 95 / ГРНТИ: 17.82.93 / ББК: 84(0)